Understanding photobooks the form and content of the photographic book - Colberg, Jörg (Routledge, 2016)
Understanding Photobooks is a user-friendly guide to engaging with the photographic book- or, as it is widely known, the photobook. Despite its importance as a central medium in which many photographers showcase their work today, there is surprisingly little information on the mechanics of the photobook: what exactly it does and how it does it. Written for makers and artists, this book will help you develop a better understanding of the images, concept, sequence, design, and production of the photobook. With an awareness of the connections between these elements, you'll be able to evaluate photobooks more clearly and easily, ultimately allowing for a deeper and more rewarding experience of the work.